Promoting Cooperation in South Asia : An Agenda for the 13th SAARC Summit - Edited By Sobhan, Rehman (Dhaka The University Press Ltd., 2004)
This volume is a compendium of the papers presented at the conference convened jointly by Wilton Park and the South Asia Centre for Policy Studies (SACEPS) which was held at Wilton Park, Sussex, UK, during 11-12 October 2004. The Wilton park conference was a follow up of the twelfth SAARC Summit held in Islamabad in January 2004, and originates from a collective endeavour to provide inputs to the Thirteen SAARC Summit scheduled to be held in Dhaka during 9-11 January 2005. Prepared by a distinguished body of experts and eminent persons from South Asia, the papers focus on a number of key aspects of South Asia Cooperation including poverty eradication, trade and commerce, transport, energy, investment, health and aso the designing of a social charter for South Asia. The volume attempts to present a road map for a South Asia Economic Union. The papers provide useful insights as regards concrete modalities to advance the cause of South Asian cooperation in the coming years. It is expected to be of enormous value to the deliberations of the 13th SAARC Summit, to the decision makers and officials in the SAARC governments, to the members of the civil society across the SAARC region engaged in the process of regional cooperation, to the members of international agencies looking for ideas on how to support regional cooperation, and to the international community interested in identifying areas of opportunity to provide support for a better life for the people of south Asia.
Include Index and Map.
Papers presented at a conference held in 2004 in Sussex, England.
Keywords: South Asia -- Commerce--International Cooperation